VTP as an Active Layer in a Vertical Organic Field Effect Transistor - Roslan, Nur Adilah; Abdullah, Shahino Mah; Halizan, Muhammad Zharfan Mohd; Bawazeer, Tahani M.; Alsenany, Nourah; Alsoufi, Mohammad S.; Abdul Majid, Wan Haliza; Supangat, Azzuliani (Springer, 2018)
In this letter, a p-type organic material from metal phthalocyanine (MPc) derivative, vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis (dimethylamino)-29H,31H-phthalocyanine (VTP) has been utilized for fabrication of an organic electronic device. Prior to the fabrication of a vertical organic field effect transistor (VOFET), fundamental work in investigating the energy level of VTP has been done through determination of oxidation and reduction potentials. Energy levels of VTP were calculated based on the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of cyclic voltammetry (CV) and UV–vis analyses. Subsequently, the soluble VTP was employed as an active layer in VOFET with different thicknesses of 90.4 nm, 66.4 nm, and 52.1 nm. It is found that a device with 66.4 nm VTP’s thickness showed the optimum performance, by giving the maximum current density and lowest threshold voltage of around 37 mA/cm2 and 7.1 V, respectively. The effects of the channel thickness on the semi-transparent VOFET devices are explained in this work.